Introducing technology to support older people living at home - a qualitative study of ethics from the perspective of care professionals - Nina Keskitalo; Sanna Viljamaa; Essi Xiong; Jukka Jauhiainen; Karoliina Paalimäki-Paakki (Finnish Social and Health Informatics Association, 2023)
Today's demographic shift towards an aging population is increasing health challenges, and technologies need to be developed to support older people. The national policy in Finland is that older people have the right to live in their own homes for as long as this is safe and meets their needs. However, introducing technology comes with ethical challenges and requires new skills of care personnel. The ethical aspects of technology need to be discussed in more depth. This study aimed to explore the ethical competence of care professionals who work with older people concerning the introduction of technology that supports living at home and to reveal the issues in this area that need development. The study was based on an electronic survey of 14 care professionals working in home care and used a descriptive qualitative study design. Inductive content analysis revealed four main categories: professional ethics, decision-making, change brought about by technology, and factors affecting the introduction of technology. This study shows that care professionals, regardless of their level or field of education, recognize professional ethics as a factor that guides their everyday work. However, it seems that ethics are not always realized in practice. To meet older peoples' needs and wishes decision-making and individual assessment play an important role when introducing technology. The introduction of technology to support living at home among older people has a strong ethical dimension and requires strong professional ethics. The present study suggests that care personnel have insights into these ethical aspects, but that training, guidelines and operative models are needed to support care professionals' ethical thinking and decision-making. The results of this study can help health care organizations identify care personnel's training needs and requirements for a clear, uniform process to introduce technology.